1984
DOI: 10.1111/j.1768-322x.1984.tb00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependent inhibition of growth: fractionation of inhibitory diffusible factor(s) released by dense cultures of 3T3 cells

Abstract: Different data have suggested that the density-dependent inhibition of growth in normal 3T3 cells is due to the release of inhibitory factor(s) into the medium. The present results provide more evidence supporting this hypothesis. From conditioned medium of dense cultures of 3T3 cells, we fractionated a thermolabile inhibitory diffusible factor (I.D.F.) with a molecular weight of about 40.000 This factor decreased the [11C]-inosine incorporation into purine nucleotides and into nucleic acids of stimulated 3T3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
12
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
5
12
0
Order By: Relevance
“…It is of interest to note that our present results help to explain our previous difficulties in showing inhibitory factors in fractions of 10-13 K MW (Harel et al, 1983). They are now in agreement with those of Steck and coworkers (1982) and Well and Malluci (19831, who demonstrated inhibitory activities in fractions 10-13 K when they were added to target cells labeled with 3H thymidine, in the presence of serum.…”
Section: Secretion B 3t3 Cells Of Stimulatory and Inhibitory Factors supporting
confidence: 94%
See 1 more Smart Citation
“…It is of interest to note that our present results help to explain our previous difficulties in showing inhibitory factors in fractions of 10-13 K MW (Harel et al, 1983). They are now in agreement with those of Steck and coworkers (1982) and Well and Malluci (19831, who demonstrated inhibitory activities in fractions 10-13 K when they were added to target cells labeled with 3H thymidine, in the presence of serum.…”
Section: Secretion B 3t3 Cells Of Stimulatory and Inhibitory Factors supporting
confidence: 94%
“…The presence of stimulating factors may mask the inhibitory ones. These results help to explain our previous dificulties in finding low molecular weight inhibitory factors (Harel et al, 1983) and they now agree with those of Steck and co-workers (1982).…”
supporting
confidence: 92%
“…On the other hand, different results have suggested that DDI of growth in 3T3 cells is under the control of growth inhibitory molecules diffusing from dense cultures (Harel et al, 1978). Growth inhibitory factors have been fractionated or purified from medium conditioned by dense cultures of 3T3 cells (Harel et al, 1983Blat et al, 1986;Hsu and Wang, 1986) and other cell types (Holley et al, 1980;Wells and Malluci, 1983;Iwata et al, 1985). However, a molecule of 25 Kd, inhibitory for BSCl cells (Holley et al, 1980), was shown to be similar to PTGF secreted by transformed and normal cells (Roberts et al, 19811, and could be a bifunctional regulator of cell growth (Tucker et al, 1984;Roberts et al, 1985;Shipley et al, 1985).…”
mentioning
confidence: 96%
“…Steck and coworkers reported partial purification from conditioned medium of 3T3 cell cultures of growth inhibitory factors (Steck et al, 1979;1982). We recently fractionated, from the culture medium of 3T3 cells, a thermolabile inhibitory diffusible factor (IDF) with a molecular weight of about 40,000 daltons (Harel et al, 1983) This factor decreased the 14C-inosine incorporation into purine nu-cleotides and nucleic acids of stimulated target 3T3 cells.In the presence of IDF, DNA synthesis and protein accumulation also decreased.To provide new evidence for the assumption that IDF is involved in the DDI of growth and to obtain further insight into the mechanism of the release of DDI of growth in transformed cells, we compared the inhibitory activity of IDFN produced by 3T3 cells and of IDFT, (produced by Rous sarcoma virus-transformed [3T3 SRAJ H] cells), on 3T3 and 3T3 SRA/H cell metabolism. …”
mentioning
confidence: 99%
“…Steck and coworkers reported partial purification from conditioned medium of 3T3 cell cultures of growth inhibitory factors (Steck et al, 1979;1982). We recently fractionated, from the culture medium of 3T3 cells, a thermolabile inhibitory diffusible factor (IDF) with a molecular weight of about 40,000 daltons (Harel et al, 1983) This factor decreased the 14C-inosine incorporation into purine nu-cleotides and nucleic acids of stimulated target 3T3 cells.…”
mentioning
confidence: 99%